Role of PTEN Gene in Progression of Prostate Cancer - Pourmand, Gholamreza; Ziaee, Abed-Ali; Salem, Sepehr; Abedi, Amir Reza; Mehrsai, Abdolrasoul; Alavi, Hossein Afshin; Ahmadi, Ali; Saadati, Hamid Reza (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to clarify the role of PTEN gene in progression of prostate cancer. Materials and Methods: A total of 51 formalin-fixed paraffin-embedded specimens of prostate cancer were analyzed for PTEN mutations. Tissue microdissection and polymerase chain reaction/single-strand conformation polymorphism methods were used. Clinical and pathologic data of the patients were reviewed with regard to PTEN mutation. Results: The Gleason score (GS) was less than 7 in 29 (56.8%), 7 in 11 (21.6%), and greater than 7 in 11 (21.6%). Tumor stage was IIa, IIb, IIc, and IV in 14 (27.4%), 4 (7.8%), 21 (41.2%), and 12 (23.6%) patients, respectively. Eleven of 12 stage IV tumors had metastases at the time of presentation. Six of 51 cases (11.6%) showed mutation in PTEN which had involved exones 1, 2, and 5. Two of these cases had localized and the others had advanced prostate cancer. One case of the tumors with PTEN mutation had a GS of 7 and 5 had GSs greater than 7. Patients with a positive mutation of PTEN had a significantly greater GS (P < .001), lower survival rate (P = .001), higher tendency to metastasis (P = .002), and higher prostate-specific antigen (P = .03). Cox proportional hazard model showed that only GS was significantly correlated with mortality (P = .03). Conclusion: Patients with prostate cancer who had PTEN mutation had also a significantly greater GS, poorer prognosis, and higher rate of metastasis. However, this mutation cannot predict the prognosis and the GS is a more precise factor.